Experimental Investigation of Ammonia/Oxygen/Argon Combustion: The Role of Equivalence Ratio and Nozzle Shape in a Constant Volume Combustion Chamber with Sub-chamber - Mitsuhisa Ichiyanagi; Emir Yilmaz; Takuma Ohashi; Masato Sanno; Guansen Lin; Sebastian Gunawan; Henry Widjaja; Leon Jonathan; Gabriel Jeremy Gotama; Willyanto Anggono; Takashi Suzuki (Journal of Engineering and Technological Sciences, 2024)
The global rise in carbon emissions presents a rising challenge for current and future generations. In the pursuit of zero carbon emissions, ammonia (NH3) has emerged as an attractive alternative energy source. Ammonia offers a carbon-free fuel option with a higher energy density than liquid hydrogen while maintaining ease of transport and storage. However, ammonia still has its drawbacks, such as a high autoignition temperature, slow burning velocity, and low heating value, that demand further investigation of its combustion characteristics. This experiment was done to study the effect of nozzle shape and equivalence ratio (ɸ) on the combustion of an ammonia/oxygen/argon mixture using a constant volume combustor equipped with a sub-chamber. The fuels were premixed for 10 minutes and conditioned to an initial pressure of 0.2 MPa and an initial mixture temperature of 423 K. The results show that the different nozzle shapes each have their advantages in terms of pressure and jet speed. Overall, the lean mixtures (ɸ0.6 and ɸ0.8) consistently performed better compared to the stoichiometric mixtures (ɸ1.0) in all categories investigated in this study. The round nozzle generates higher pressure, while the special shape nozzle enhances jet speed, highlighting trade-offs between the two.